STUDENTS’ ATTITUDE TOWARDS VIDEO CONFERENCING APPLICATION IN LEARNING SPEAKING SKILLS IN INDONESIAN HIGHER EDUCATION - Wulan Nia Umroh; Munir Munir; A. Muliati (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This study aims to describe students‘ perceptions of the use of Google Meet in learning the English process. This research took place at the State University of Makassar. The population of this research was the student of the State University of Makassar. The researcher used the interview as an instrument to obtain the data. Based on the result of the study, the researchers found that the students show a positive and negative attitude toward video conferencing through Google meet in the learning process. The positive attitude shown by the students is: showing their readiness to engage during video conferencing, showing enthusiasm for a range of movements during video conferencing, developing their skills to utilize the learning tools, and showing respect and appreciation the others’ ability and disability. While the negative attitude was the students don’t attend class and did not participate in the group project as well, and also if they cannot speak as well during video conferencing, they wouldn’t participate in the class, they decided to keep silent and not follow the instruction from the lecturer.